2020
DOI: 10.1002/ccd.29111
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Coated balloons vs drug‐eluting stents for the treatment of small coronary artery disease: A meta‐analysis of randomized trials

Abstract: Objectives and background There is conflicting evidence about the effects of drug‐coated balloons (DCB) compared with drug‐eluting stents (DES) in patients with native small vessel coronary artery disease (CAD). Methods The PubMed, Embase, Cochrane Central Register of Controlled Trials, and http://ClinicalTrials.gov databases and main international conference proceedings were searched for randomized controlled trials (RCT) comparing DCB versus DES in patients with native small vessel CAD. Data were pooled by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…In fact, the use of DCBs in anatomic settings adverse for treatment with DESs was not only shown to be similarly efficacious but also safer, as shown by the reduced risk of vessel thrombosis with DCBs than with DESs in patients with small vessel CAD. 47,48 Two early randomized clinical trials have reported conflicting results about the effects of DCBs compared with early-generation DESs on angiographic outcomes in patients with native small vessel CAD. 12,49 More recently, larger randomized trials with the use of second-generation DESs and novel DCB devices provided new evidence about the clinical and angiographic effects of these treatments.…”
Section: Dcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the use of DCBs in anatomic settings adverse for treatment with DESs was not only shown to be similarly efficacious but also safer, as shown by the reduced risk of vessel thrombosis with DCBs than with DESs in patients with small vessel CAD. 47,48 Two early randomized clinical trials have reported conflicting results about the effects of DCBs compared with early-generation DESs on angiographic outcomes in patients with native small vessel CAD. 12,49 More recently, larger randomized trials with the use of second-generation DESs and novel DCB devices provided new evidence about the clinical and angiographic effects of these treatments.…”
Section: Dcbsmentioning
confidence: 99%
“…11,12,36 A recent meta-analysis has shown that the use of paclitaxel-releasing DCB is associated with risks of target vessel revascularization and restenosis that are similar to DES (odds ratio [OR], 0.97; 95% CI, 0.56-1.68; P ¼ .92 and OR, 1.12; 95% CI, 0.69-1.84; P ¼ .64, respectively), whereas DCB yielded to a significant reduction in the risk of vessel thrombosis (OR, 0.12; 95% CI, 0.01-0.94; P ¼ .04) and DES implantation resulted in slightly better angiographic surrogate end points at the mid-term follow-up. 47 However, a recent observational study that included a nationwide cohort of 14,788 patients who underwent PCI with DCBs or DESs for small vessel CAD (defined as 2.5 mm, but inferred by the size of the implanted device) showed that treatment with DCBs compared with DESs was associated with a significantly higher risk for restenosis (hazard ratio, 2.02; 95% CI, 1.54-2.67; P < .001) and a similar risk of target lesion thrombosis, MI, and all-cause death. 50…”
Section: Dcbsmentioning
confidence: 99%
“…Contrary to our findings, Jalaluddin reported a significantly higher MACE events (4.3% vs. 0.6%; P =0.000), MI (2.6% vs. 0.4%; P =0.002) in the diabetic group [ 37 ]. A meta-analysis by Sánchez et al reported that diabetes did not affect the effect of DCB on the TVR [ 44 ]. These conflicting results might be related on the one hand to the differences in the inclusion criteria; only patients with ≤2.75 mm vessel diameter were enrolled, and all bailout stenting were excluded from our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jalaluddin included all patients regardless of the vessel size [ 37 ]. Concerning the meta-analysis by Sánchez et al, the heterogeneity of the included trials in terms of the vessel size (<3 mm, <2.8 mm, and ≤2.75 mm) is significant to consider, knowing that the risk of restenosis after PCI is inversely correlated to the treated vessel's size [ 12 , 44 , 45 ]. The enrolled trials included the bailout BMS implantation cases, besides, procedural limitations such as the absence of routine lesion pre dilatation in the PICCOLETO trial, and heterogeneity in the duration of the follow-up among the included trials [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of late lumen loss (LLL) and instent restenosis (ISR) is reduced. Substantial evidence has accumulated over the past years in ISR and de novo large or small coronary lesions (8)(9)(10). Very small vessels (VSV; lumen diameter <2 mm) lesions are common in coronary arteries especially in the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%